PERILAKU MEROKOK TERHADAP KEBUGARAN JASMANI SISWA LAKI-LAKI SMA NEGERI 22 SIGI : Indonesia - Murtono, Tri; Arief Aditya Rifandy; Delvi Kristanti Liloi; Rahmah; Fila Delfia (UNIB Press, 2025)
This research is a quantitative research with a descriptive correlational approach. This research aims to determine the relationship between smoking behavior and physical fitness in male students ofJunior High School 22 Sigi. The sample used in this study were 10 male students in grades VII and VIII of Junior High School 22 Sigi. Based on the results of data analysis, it can be concluded that the level of physical fitness of students who are classified as smokers tends to be low. Of the 10 smoker students, only 2 students (20%) have physical fitness in the